IDENTIFICATION OF PASSIVE STRATEGIES FOR SUSTAINABLE CONSTRUCTION, ON VERNACULAR ARCHITECTURE OF ECUADOR - Pérez, Marina; Eskola, Freddy; Guzmán, Sebastián; Rosas, Paz; Tapia, Emilia (European Scientific Journal, ESJ, 2015)
The main goal of the article is to share the preliminary results of the research project “Architecture and Building Ecuador Involved in the work of the Sustainable Construction” in Strategies for Energy efficiency. In this stage it was identified the sustainable criteria of vernacular architecture in Ecuador, from the specific analysis of homes located south of the country, in the provinces of Azuay and Cañar, with temperatures of 6-20° C, which in these latitudes are considered temperate to cold. The research selected houses with traditional construction systems, such as adobe rammed earth, tapial and mixed systems, as these are the ones that represent the traditional architecture of the study area. Subsequently it was performed a critical analysis to identify the passive strategies used to face the environmental conditions, such as: location, sunlight and ventilation, which improve the thermal and light quality inside homes. In conclusion, the article aims put into consideration the advances in the identification of the vernacular architecture characteristic even when performed without specific knowledge of sustainability has been made comfortable thermal and lighting spaces, with passive strategies.